Effect of oral care program on prevention of ventilator-associated pneumonia in intensive care unit patients: A randomized controlled trial - Vajihe Atashi; Hojatollah Yousefi; Hosein Mahjobipoor; Reza Bekhradi; Ahmadreza Yazdannik (Wolters Kluwer Medknow Publications, 2018)
Background: Ventilator-associated pneumonia (VAP) is one of the most common nosocomial infections that increase mortality rate and the length of hospitalization. Oral care can improve patient's oral health, however, the role of oral care in the reduction in incidence rate of VAP is indisputable. The aim of this study was to investigate the effect of oral care on the frequency of VAP of patients in intensive care unit. Materials and Methods: This clinical trial was conducted on 80 participants who were randomly assigned to a control group and an intervention group from 2016 to 2017. Data were collected at the first, third, and fifth days of the study using a demographic and clinical characteristics questionnaire and the Clinical Pulmonary Infection Score for detecting pneumonia. Data analysis was performed using descriptive and inferential statistics in SPSS software. Results: The results of this study showed that the frequency of pneumonia on the third and fifth days was 15.80% (6) and 23.70% (9) in the control group and 10.50% (4) and 7.90% (3) in the intervention group, respectively. Chi-square test did not show a significant difference (p = 0.059); however, the frequency of pneumonia in the intervention group reduced compared with the control group. Conclusions: According to the results of this study, the oral care program could not significantly decrease the incidence of VAP in critically ill patients compared with routine oral care practices. Similar studies with a larger sample size and longer duration should be conducted for better results.